Pancasila Sebagai Landasan Dalam Membentuk Masyarakat yang Berintegritas - Fikri, Muhammad Zaki (Maliki Interdisciplinary Journal, 2026)
Pancasila is the primary philosophical foundation for shaping an Indonesian society with high integrity. The five values ​​contained within Pancasila provide a comprehensive framework of values. The principle of Belief in God and Humanity underpins moral values, honesty, and individual responsibility. The principle of Unity emphasizes the public interest over personal interests. Meanwhile, the principle of Democracy and Social Justice guarantees accountability, transparency, and egalitarianism. However, several obstacles exist in implementing Pancasila values ​​in public life. Internal problems such as corruption and nepotism in government and the influx of foreign cultures due to globalization further exacerbate the situation. Therefore, Pancasila serves as a foundation or moral foundation for all elements of society. Consistent internalization of these values ​​is a strategic key in building a strong culture of integrity and ensuring the achievement of the ideals of social justice. The practice of Pancasila is crucial in realizing an honest, just, and responsible society.